2018
DOI: 10.1080/10717544.2018.1440664
|View full text |Cite
|
Sign up to set email alerts
|

New model of proliferative vitreoretinopathy in rabbit for drug delivery and pharmacodynamic studies

Abstract: Blinding retinal diseases become more epidemic as the population ages. These diseases, such as diabetic retinopathy and macular edema, are of chronic nature and require protracted drug presence at the disease site. A sustained intravitreal porous silicon delivery system with dexamethasone (pSiO2-COO-DEX) was evaluated in a new rabbit model of proliferative vitreoretinopathy (PVR) in a real treatment design. In contrast to the pretreatment design model, pSiO2-COO-DEX was intravitreally injected into the eyes wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…While the rabbit is a commonly utilized animal model for PVR due to the large size of the globe and its ability to manifest features similar to the human condition, existing models have not consistently demonstrated both epi-and subretinal membranes, the key histologic features of human PVR. 16,29,[39][40][41][42][43][44][45][46] In addition, our data demonstrate the involvement of multiple collagen species in the development of PVR membranes, suggesting that multiple profibrotic signaling pathways may be involved. These rabbit data also validate the presence of additional features of human PVR, i.e., increased microglial invasion into epiretinal membranes, Mϋller glia activation, and RPE de-differentiation.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…While the rabbit is a commonly utilized animal model for PVR due to the large size of the globe and its ability to manifest features similar to the human condition, existing models have not consistently demonstrated both epi-and subretinal membranes, the key histologic features of human PVR. 16,29,[39][40][41][42][43][44][45][46] In addition, our data demonstrate the involvement of multiple collagen species in the development of PVR membranes, suggesting that multiple profibrotic signaling pathways may be involved. These rabbit data also validate the presence of additional features of human PVR, i.e., increased microglial invasion into epiretinal membranes, Mϋller glia activation, and RPE de-differentiation.…”
Section: Discussionmentioning
confidence: 53%
“…29 Elevated αSMA expression in epiretinal membranes at time points ranging from 22 days to 11 weeks post-induction have been reported, but subretinal data are unavailable. 29,[42][43][44][45][46] Khanum et al reported evaluation of their rabbit model one and 30 days postinduction; however, it is unclear from their figures from which time points their photomicrographs of H&E-stained or immunolabeled sections were obtained. 40 Our 6hour and 2-day data broadly align with the findings of Zahn et al at days 3 and 7 postinduction, in which they assayed Mϋller glia, microglia, and macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…After injecting the cells, PP/Sh was injected from another location in the same eye. As the vitreous volume of rabbits was 1.2–1.5 ​mL [ 71 ], according to cytotoxicity and cell transfection experiments, the amount of plasmid transfected in the treatment group (called ARPE ​+ ​PP/Sh) was 4 ​μg. In the control group (labeled as PBS), the negative control group (labeled as ARPE ​+ ​PP/DNA), and the security testing group (labeled as PP/DNA), the injected DNA (or PEI-g-PEG) concentration and PBS volume remained unchanged to maintain the total amount of transfected DNA constant among the groups [ 72 ].…”
Section: Methodsmentioning
confidence: 99%
“…This is because pigmented rabbits exhibit drug interactions with ocular pigments that are more representative of human eyes. Conversely, investigating drug pharmacokinetics is the main goal, this interaction could be a confounder, and the use of albino rabbits is advised [78]. A study by Sinapis et al that investigated the pharmacodynamics of intravitreal bevacizumab at a dose of 1.25 mg/50 μL in rabbit eyes found differences in bevacizumab concentrations in the intravitreal space, anterior chamber, blood serum, and contralateral eye following injection.…”
Section: Intravitreal Injection For Pvr Prevention In Ogimentioning
confidence: 99%
“…After intravitreal bevacizumab injection, traces of bevacizumab were also found in distant organs such as the brain, heart, liver, and colon. It is suspected that the drug passes through the retinal-ocular barrier and enters the bloodstream [78,79]. Further research is needed to understand the drug's impact on other organs.…”
Section: Intravitreal Injection For Pvr Prevention In Ogimentioning
confidence: 99%